The curious case of impairment and the school textbook - Alan Hodkinson; Amir B Ghajarieh (Educational Futures, 2014)
This ‘think piece’ re-casts the school textbook as ontological envelopes which enfold an unresolved dialectic between constituting and constituted power into the education of every school pupil. Informed by the writings of Deleuze and Guattari (1987) the authors reveal that textbooks act as ‘majoritan’ to categorise, contain and constrain societal conceptions of the ‘Other’. The authors propose that educators must reinvent notions of freedom, authority and ethical responsibility. The authors conclude that to undermine the pernicious power of the ‘normalising’ textbook we need the production of a counter signifying semiotic to overcome pathologies existing in schools today.